2016
DOI: 10.1177/1687814016674627
|View full text |Cite
|
Sign up to set email alerts
|

Bond strength between carbon fiber–reinforced plastic tubes and aluminum joints for racing car suspension

Abstract: According to previous studies, the bond strength between the carbon fiber-reinforced plastics and metals mainly depends on the bond layer between the carbon fiber-reinforced plastic composites and the metal. This article presents the results of the experiments conducted on the tensile bond strength between the carbon fiber-reinforced plastic tubes and aluminum joints. The parameters examined in these experiments include adhesive type, surface roughness of the bonded area, and thickness and length of the bond l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
0
7
1
Order By: Relevance
“…The last step of the theoretical design focused on researching the results obtained by other teams. There has been an interesting approach made by the Harbin Racing Team [ 11 ], where the results showed that the ultimate tensile force for a tested bond was at maximum when the bond gap was 0.2 mm. Additionally, the length of a bond increased its strength linearly.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The last step of the theoretical design focused on researching the results obtained by other teams. There has been an interesting approach made by the Harbin Racing Team [ 11 ], where the results showed that the ultimate tensile force for a tested bond was at maximum when the bond gap was 0.2 mm. Additionally, the length of a bond increased its strength linearly.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the design must be validated by real life testing, which should answer the question which epoxy adhesive is optimal for the final wishbone as well as determine the proper gap control method. Having said that, the results obtained from experiments will be contrasted with the achievements of other teams in wishbone design and testing [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, carbon fiber reinforced polymer (CFRP) has emerged as one of the notable accepted retrofitting materials of the civil engineering community in recent years [1]. Several studies account the success of CFRP as reinforcement in a wide variety of applications for different materials such as aluminum [2,3], steel [4,5], and concrete [6][7][8]. The utilization of CFRP as retrofitting material provides technically sound and cost-efficient due to its lightweight, resistance to corrosion, and ease of handling and installation [9][10][11].…”
Section: Introductionmentioning
confidence: 99%